Al2O3:C and LiF: Mg, Ti characterisations at 100–150 kV energy range for computed tomography dose measurement. (October 2022) - Omar, R.S.; Hashim, S.; Bradley, D.A.; Karim, M.K.A.; Kobayashi, I.; Kadir, A.B.A.; Hashim, A.
Abstract: Performance characterisation has been carried out of nanoDot™ OSLDs and TLD-100™, validating their use for diagnostic x-ray dose profile assessments. Investigations include optical annealing, signal depletion, signal fading, dose-response, sensitivity, and energy dependence. Both dosimeter types were exposed using the Constant Potential Industrial X-ray (Model Philips MG 165) in Standard Radiation Qualities (RQT) procedure located in Nuclear Malaysia, Bangi. OSLD annealing using a 14 W compact fluorescent lamp showed an average signal loss of ∼93% as a result of 60 min of illumination. For dosimetric signal depletion, screened nanoDot™ OSLDs gave rise to the most favorable performance, with a mean signal loss of 1.0% per reading. In respect of signal fading, similar favorable performance was found for the screened nanoDot™ OSLDs, after a stabilisation period of 11–12 days post-irradiation, the average reading decreased by ∼1% over a further 17 days. For doses up to 500 mGy the TLD-100™ and screened nanoDot™ OSLDs both provide a highly linear response, with a regression coefficient of 0.999 in both cases. Linear energy dependence was found for RQT spectra from 100 to 150 kV. Highlights: The validation of nanoDot™ OSLDs and TLD-100™ were confirmed by the energy dependence up to 150 kV. Dose-response behavior tends to display a linear behavior at 100–150 kV energy range. A compact fluorescent lamp provided a short annealing time; alternatively, can replace the OSLD annealer. Light output constancy is gained from the use of the optical annealing method.